Correlation between septal midwall late gadolinium enhancement on CMR and conduction delay on ECG in patients with nonischemic dilated cardiomyopathy. (February 2020) - Becker, Marthe A.J.; Allaart, Cornelis P.; Zweerink, Alwin; Cornel, Jan H.; van de Ven, Peter M.; van Rossum, Albert C.; Germans, Tjeerd
Abstract: Background: Septal midwall late gadolinium enhancement (LGE) on cardiac magnetic resonance imaging (CMR) is a characteristic finding in nonischemic dilated cardiomyopathy (DCM) and is associated with adverse cardiac events. QRS-prolongation in DCM is also frequently present and a predictor of arrhythmic events and mortality. Since the His-Purkinje fibres are located in the interventricular septum, QRS-prolongation may directly result from septal fibrosis, visualized by LGE. Our aim was to study the correlation of the presence and extent of septal midwall LGE and QRS-duration. Methods: DCM-patients with left ventricular (LV) dysfunction (LVEF < 50%) were included. LV volumes, systolic function and nonischemic septal midwall LGE, defined as patchy or stripe-like LGE in the septal segments, were quantified. QRS-duration on standard 12-lead ECG was measured. Results: 165 DCM-patients were included (62% male, mean age 59 ± 15 years) with a median LVEF of 36% [24–44]. Fifty-one patients (31%) demonstrated septal midwall LGE with a median extent of 8.1 gram [4.3–16.8]. Patients with midwall LGE had increased LV end-diastolic volumes (EDV) 248 mL [193–301] vs. 193 mL [160–239], p < 0.001) and lower LVEF (26% [18–35] vs. 40% [32–45], p < 0.001). Median QRS-duration was 110 ms [95–146] without a correlation to the presence nor extent of midwall LGE. QRS-duration was moderately correlated with LV-dilation and mass (respectively r = 0.35, p < 0.001 and r = 0.30, p < 0.001). Conclusion: In DCM-patients, QRS-prolongation and septal midwall LGE are frequently present and often co-exist. However, they are not correlated. This suggests that the assessment of LGE-CMR has complementary value to ECG evaluation in the clinical assessment and risk stratification of DCM-patients.